KEANEKARAGAMAN JENIS JAMUR MAKROSKOPIS PADA BERBAGAI KONDISI TEMPAT TUMBUH HUTAN RAWA GAMBUT DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS UNIVERSITAS TANJUNGPURA - Utama, Syapriadi; Astiani, Dwi; Ekyastuti, Wiwik (Universitas Tanjungpura, 2019)
Tanjungpura University Forest for Special Purpose located in three districts Landak Regency, Mempawah Regency and Kubu Raya Regency. Has the potential to use and process non-timber forest products. The diversity of macroscopic fungi is not yet known as one of the potential natural biological resources of significant value. So that a mushroom inventory must be carried out to identify and assess the diversity of macroscopic fungi. The method used is the survey method. Data retrieval uses a double plot sampling technique. The size of each observation plot is 5 m Ã— 5 m as the initial reference, four plots in the peat swamp forest area with open canopy cover conditions and also four observation plots in peat swamp forest areas with canopy cover conditions are still closed. Placement of research plots in both areas was carried out purposively in locations where there were many types of macroscopic fungi. The results showed that the types of macroscopic fungi found at the study site were 24 species. 24 species were divided into 594 individuals belonging to 23 genera and 9 families. Macroscopic fungi found in open canopy cover were found in 17 species, while in closed canopy cover there were 13 species. In both types of conditions the place to grow has the same 6 types of fungi. The degree of diversity of macroscopic fungi in various conditions the peat swamp in Tanjungpura University Forest for Special Purpose is low.Keyword: Macroscopic fungi, peat swamp forest, Tanjungpura University Forest for Special Purpose.